Coupling Mechanical and Electrical Properties in Spin Crossover Polymer Composites. Issue 8 (8th January 2018) - Rat, Sylvain; Piedrahita‐Bello, Mario; Salmon, Lionel; Molnár, Gábor; Demont, Philippe; Bousseksou, Azzedine
Abstract: Spin crossover particles of formula [Fe{(Htrz)2 (trz)}0.9 (NH2 ‐trz)0.3 ](BF4 )1.1 and average size of 20 nm ± 8 nm are homogeneously dispersed in poly(vinylidene fluoride‐co‐trifluoro‐ethylene), P(VDF‐TrFE), and poly(vinylidene fluoride) (PVDF) matrices to form macroscopic (cm‐scale), freestanding, and flexible nanocomposite materials. The composites exhibit concomitant thermal expansion and discharge current peaks on cycling around the spin transition temperatures, i.e., new "product properties" resulting from the synergy between the particles and the matrix. Poling the P(VDF‐TrFE) (70–30 mol%) samples loaded with 25 wt% of particles in 18 MV m −1 electric field results in a piezoelectric coefficient d 33 = −3.3 pC N −1 . The poled samples display substantially amplified discharges and altered spin transition properties. Analysis of mechanical and dielectric properties reveals that both strain (1%) and permittivity (40%) changes in the composite accompany the spin transition in the particles, giving direct evidence for strong electromechanical couplings between the components. These results provide a novel route for the deployment of molecular spin crossover materials as actuators in artificial muscles and generators in thermal energy harvesting devices. Abstract : P(VDFTrFE) and poly(vinylidene fluoride) (PVDF) composites of spin transition nanoparticles are synthesized to obtain flexible, freestanding, macroscopic objects displaying original electromechanical properties. The synergy between the components leads to concomitant thermal expansion and electrical discharge peaks at the spin transition providing scope for the deployment of spin crossover materials as actuators in artificial muscles and generators in thermal‐energy‐harvesting devices.